Optical properties of Mn-doped CdS thin films grown by the SILAR method - N Phasook; S Kamoldirok; W Yindeesuk (My University, 2018)
In this research, the manganese doped cadmium sulfide (Mn-doped CdS) thin films were synthesized on glass substrates using successive ionic layer adsorption and reaction (SILAR) method. The thin films were prepared by different mixing percentage of manganese with cadmium sulfide precursors in the range of 1 - 20 mole%. The optical properties were investigated by ultraviolet-visible spectrophotometer. The morphology and elemental analysis were measured by scanning electron microscopy (SEM) and energy dispersive x-ray spectroscopy (EDS), respectively.
Keywords: Cadmium sulfide; Energy-dispersive X-ray spectroscopy; Quantum Dots Synthesis And Properties